Performance Testing of a Multicylinder Diesel Engine Using Antioxidant Bio-Oil Additives from Moringa Oleifera Leaf Pyrolysis - Jeri Juliyono; Sonika Maulana; Rizqi Fitri Naryanto; Angga Septiyanto (JMEL : Journal of Mechanical Engineering Learning, 2025)
Crude oil reserves are steadily depleting. One viable alternative is the use of biodiesel fuel in diesel engines. However, a major drawback of biodiesel is its susceptibility to degradation due to low oxidative stability. Antioxidants are compounds that inhibit or slow down the oxidation process by preventing the formation of oxidants or reducing the propagation of free radicals. This study aims to investigate the effect of adding antioxidant additives derived from Moringa oleifera bio-oil, produced through pyrolysis, to B30 biodiesel fuel at concentrations of 0, 500, 1000, and 1500 ppm on the performance of a multicylinder diesel engine. A quantitative approach was employed using an experimental method, and data analysis was conducted using descriptive analysis. The results showed that fuel consumption decreased with the addition of Moringa oleifera antioxidants, with reductions of 5.31%, 6.66%, and 7.08% at 500 ppm, 1000 ppm, and 1500 ppm, respectively, at an engine speed of 2500 rpm. The highest torque was achieved with 1000 ppm of Moringa oleifera antioxidant at 2728 rpm, reaching 111.9 Nm (an increase of 4.48%), while the highest power output was also obtained at 1000 ppm, reaching 70.9 HP at 5100 rpm (an increase of 3.2%).